2022
DOI: 10.1016/j.isci.2022.103789
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide functional head on short-chain perfluorinated substance drives developmental toxicity

Abstract: Summary Per- and polyfluoroalkyl substances (PFAS) are ubiquitously detected in environmental and biological samples and cause adverse health effects. Studies have predominately focused on long-chain PFAS, with far fewer addressing short-chain alternatives. This study leveraged embryonic zebrafish to investigate developmental toxicity of a short-chain series: perfluorobutane sulfonate (PFBS), perfluoropentanoic acid (PFPeA), perfluorobutane sulfonamide (FBSA), and 4:2 fluorotelomer sulfonic acid (4:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Federal and state regulatory efforts are presently focused on legacy PFAS predominantly detected in water and do not consider the full range of highly bioaccumulative terminal PFAA and precursors discussed in this work. Metabolism of precursors that exhibit a higher bioaccumulation potential than their terminal degradation products will enhance exposures to terminal PFAA of concern. , Some studies have suggested sulfonamide precursors have greater bioactivity than PFAA of similar perfluorinated carbon chain length due to their higher pKa, greater fraction of neutral species at similar pH, and interactions with lipids and membranes facilitated by the sulfonamide head group. , Additional physicochemical and toxicological data on diverse precursors, particularly the sulfonamides, are needed to better understand their bioaccumulation potential and toxicity. Our work suggests that more comprehensive fish advisories are needed to account for potential human exposures to the full suite of highly bioaccumulative longer-chain PFAA and ECF precursors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Federal and state regulatory efforts are presently focused on legacy PFAS predominantly detected in water and do not consider the full range of highly bioaccumulative terminal PFAA and precursors discussed in this work. Metabolism of precursors that exhibit a higher bioaccumulation potential than their terminal degradation products will enhance exposures to terminal PFAA of concern. , Some studies have suggested sulfonamide precursors have greater bioactivity than PFAA of similar perfluorinated carbon chain length due to their higher pKa, greater fraction of neutral species at similar pH, and interactions with lipids and membranes facilitated by the sulfonamide head group. , Additional physicochemical and toxicological data on diverse precursors, particularly the sulfonamides, are needed to better understand their bioaccumulation potential and toxicity. Our work suggests that more comprehensive fish advisories are needed to account for potential human exposures to the full suite of highly bioaccumulative longer-chain PFAA and ECF precursors.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 70 Some studies have suggested sulfonamide precursors have greater bioactivity than PFAA of similar perfluorinated carbon chain length due to their higher pKa, greater fraction of neutral species at similar pH, and interactions with lipids and membranes facilitated by the sulfonamide head group. 69 , 71 73 Additional physicochemical and toxicological data on diverse precursors, particularly the sulfonamides, are needed to better understand their bioaccumulation potential and toxicity. Our work suggests that more comprehensive fish advisories are needed to account for potential human exposures to the full suite of highly bioaccumulative longer-chain PFAA and ECF precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies with PFOS and 6:2 FTS can build upon this study by focusing on the dose range between 100 and 2000 μg/L (PFOS equivalents) to determine whether there is a predictable threshold effect within this range where the interaction shifts from less-than-additive to more-than-additive, and whether that threshold changes with ratios different from the approximate range 1:10–1:30 (PFOS to 6:2 FTS) examined in this study. In addition, concurrent evaluations of gene expression [ 33 , 34 ] would further elucidate potential modes of action that may explain the interactions observed with mixtures of PFOS and 6:2 FTS.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups [ 15 , 16 ] have reported increased risks of autism spectrum disorder at age 3 with prenatal PFOA and PFNA exposures. Animal studies also support concerns for the neurodevelopmental risks posed by PFAS [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 94%